2012
DOI: 10.1186/1471-2369-13-76
|View full text |Cite
|
Sign up to set email alerts
|

Is serum phosphorus control related to parathyroid hormone control in dialysis patients with secondary hyperparathyroidism?

Abstract: BackgroundElevated serum phosphorus (P) levels have been linked to increased morbidity and mortality in dialysis patients with secondary hyperparathyroidism (SHPT) but may be difficult to control if parathyroid hormone (PTH) is persistently elevated. We conducted a post hoc analysis of data from an earlier interventional study (OPTIMA) to explore the relationship between PTH control and serum P.MethodsThe OPTIMA study randomized dialysis patients with intact PTH (iPTH) 300–799 pg/mL to receive conventional car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Etelcalcetide treatment resulted in a decrease in serum phosphate in all PTH strata, but the decrease was most pronounced in patients with the highest PTH concentrations at baseline, despite the fact that etelcalcetide-treated patients with the most severe sHPT were also on the highest dose of vitamin D at the end of the trial, suggesting that reductions in serum calcium and phosphate induced by etelcalcetide may have facilitated VDRA use, which would tend to increase serum phosphate via intestinal absorption of dietary phosphate. These data are consistent with previously published cinacalcet studies and suggest that calcimimetic-induced reductions in PTH may help mitigate hyperphosphatemia in patients on dialysis by decreasing phosphate efflux from the bone 11, 13, 14. Patients initiated on etelcalcetide in the lowest PTH stratum were most likely to achieve combined PTH and phosphate targets, once again highlighting the potential benefits of initiating treatment at earlier stages of the disease process.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Etelcalcetide treatment resulted in a decrease in serum phosphate in all PTH strata, but the decrease was most pronounced in patients with the highest PTH concentrations at baseline, despite the fact that etelcalcetide-treated patients with the most severe sHPT were also on the highest dose of vitamin D at the end of the trial, suggesting that reductions in serum calcium and phosphate induced by etelcalcetide may have facilitated VDRA use, which would tend to increase serum phosphate via intestinal absorption of dietary phosphate. These data are consistent with previously published cinacalcet studies and suggest that calcimimetic-induced reductions in PTH may help mitigate hyperphosphatemia in patients on dialysis by decreasing phosphate efflux from the bone 11, 13, 14. Patients initiated on etelcalcetide in the lowest PTH stratum were most likely to achieve combined PTH and phosphate targets, once again highlighting the potential benefits of initiating treatment at earlier stages of the disease process.…”
Section: Resultssupporting
confidence: 89%
“…Baseline serum phosphate concentrations were highest in patients with the highest baseline PTH. The direct correlation of PTH and phosphate has been consistently observed in other studies 8 and suggests a role of PTH-mediated bone resorption as a contributor to the development of hyperphosphatemia (endogenous hyperphosphatemia) in patients with little or no residual kidney function, as well as the stimulatory effect of phosphate on the parathyroid gland 9, 10, 11. Dietary phosphate restriction will not correct endogenous hyperphosphatemia.…”
Section: Resultsmentioning
confidence: 89%
“…By contrast, phosphorus levels in some patients were unaffected or decreased in response to cinacalcet, possibly because of better control of PTH levels. Rodriguez et al [31] showed a strong association between PTH and phosphorus concentrations, and Frazão et al [32] demonstrated better control of phosphorus levels in dialysis patients when PTH levels were effectively decreased by cinacalcet or conventional treatment with vitamin D and its analogs and/or phosphate binders [32]. Consequently, better control of PTH levels through cinacalcet treatment might have maintained or decreased the phosphorus levels in some non-dialysis patients in our study.…”
Section: Discussionsupporting
confidence: 57%
“…Increases in intestinal phosphorus absorption induced by vitamin D therapy thus likely obscure any beneficial effect of reducing PTH levels on serum phosphorus concentrations. Data reported recently, however, suggest that serum phosphorus levels are better controlled when plasma PTH levels are managed effectively either with a calcimimetic agent or with vitamin D analogs [23]. …”
Section: Discussionmentioning
confidence: 99%